Nuclear receptor activation shapes spatial genome organization essential for gene expression control: lessons learned from the vitamin D receptor. Issue 7 (23rd March 2022) - Warwick, Timothy; Schulz, Marcel H; Gilsbach, Ralf; Brandes, Ralf P; Seuter, Sabine
Abstract: Spatial genome organization is tightly controlled by several regulatory mechanisms and is essential for gene expression control. Nuclear receptors are ligand-activated transcription factors that modulate physiological and pathophysiological processes and are primary pharmacological targets. DNA binding of the important loop-forming insulator protein CCCTC-binding factor (CTCF) was modulated by 1α, 25-dihydroxyvitamin D3 (1, 25(OH)2 D3 ). We performed CTCF HiChIP assays to produce the first genome-wide dataset of CTCF long-range interactions in 1, 25(OH)2 D3 -treated cells, and to determine whether dynamic changes of spatial chromatin interactions are essential for fine-tuning of nuclear receptor signaling. We detected changes in 3D chromatin organization upon vitamin D receptor (VDR) activation at 3.1% of all observed CTCF interactions. VDR binding was enriched at both differential loop anchors and within differential loops. Differential loops were observed in several putative functional roles including TAD border formation, promoter-enhancer looping, and establishment of VDR-responsive insulated neighborhoods. Vitamin D target genes were enriched in differential loops and at their anchors. Secondary vitamin D effects related to dynamic chromatin domain changes were linked to location of downstream transcription factors in differential loops. CRISPR interference and loop anchor deletion experiments confirmed the functional relevance of nuclear receptor ligand-induced adjustments of the chromatin 3D structure for gene expression regulation.